Segmented nanofibers of spider dragline silk: Atomic force microscopy and single-molecule force spectroscopy - Oroudjev, E. (The National Academy of Sciences, 2002)
Despite its remarkable materials properties, the structure of spider dragline silk has remained unsolved. Results from two probe microscopy techniques provide new insights into the structure of spider dragline silk. A soluble synthetic protein from dragline silk spontaneously forms nanofibers, as observed by atomic force microscopy. These nanofibers have a segmented substructure. The segment length and amino acid sequence are consistent with a slab-like shape for individual silk protein molecules. The height and width of nanofiber segments suggest a stacking pattern of slab-like molecules in each nanofiber segment. This stacking pattern produces nano-crystals in an amorphous matrix, as observed previously by NMR and x-ray diffraction of spider dragline silk. The possible importance of nanofiber formation to native silk production is discussed. Force spectra for single molecules of the silk protein demonstrate that this protein unfolds through a number of rupture events, indicating a modular substructure within single silk protein molecules. A minimal unfolding module size is estimated to be around 14 nm, which corresponds to the extended length of a single repeated module, 38 amino acids long. The structure of this spider silk protein is distinctly different from the structures of other proteins that have been analyzed by single-molecule force spectroscopy, and the force spectra show correspondingly novel features.